PERAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA GURU - Jimmi Yuliandri; Muhammad Kristiawan (Jurnal Dosen Universitas PGRI Palembang)
Abstract: This study was conducted in order to reveal the role of principal leadership on improving teacher’s performance. The data were obtained through interview, documentation and observation. An increase of teachers’ performance may also improve the quality of education and quality of teaching. To achieve eligibility standards and good performance, the school needs to be headed by a Principal whom qualified with extensive knowledge about the Leadership. A schoolprincipal is responsible for the educational organization, school administration, utilization and maintenance of facilities and infrastructure, and coaching educational personnel. No matter how perfect the teaching facility, otherwise when the headmaster as executor is unable to perform his duties as an educational leader, then the success of education in schools would be difficult to achieve.Keywords: Leadership, Principal, Teachers’ Performance